Evaluasi Struktur Anggaran Dan Neraca Untuk Optimalisasi Pengambilan Keputusan Manajerial Di PT. Pandu Sejahtera Utama - Rafifah, Najla; Aulia, Zaskia Debi; Anggraeni, Annisa Wulan; Syahwildan, Muhamad (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to evaluate the structure of budgeting and balance sheets as a basis for managerial decision-making at PT. Pandu Sejahtera Utama. Effective financial management is essential for corporate sustainability, and instruments such as budgets and balance sheets play a critical role in planning, controlling, and evaluating financial performance. A descriptive quantitative case study approach was employed, utilizing financial reports from 2022–2024 and structured interviews with management regarding budgeting and financial reporting processes. The analysis includes variance analysis between budget and actual performance, as well as financial ratio analysis to assess the company’s financial position. The study is expected to provide a comprehensive overview of the effectiveness of the company’s financial system, identify discrepancies that affect operational efficiency, and offer strategic recommendations to enhance managerial decision-making. The findings are also expected to contribute academically to the development of integrated budget and balance sheet evaluation practices for medium-sized enterprises.